Levantamento de Plantas infestantes na Safra de Soja 2019-2020 - Tosta, Lucas Silva (Universidade Federal do Tocantins, 2021)
The present article refers to all activities that were performed during the internship, focusing on precision agriculture and parasitic weed control, where he was accompanied by the company Singular Agro. Damaged plants can cause variations of 10 to 90% in the competition for nutrients, light and water, in addition to being able to host pests and increase the costs of cleaning and cleaning. Losses such as these are reduced by handling the crop with the decision to take and evaluate the benefit of the applications. Various control methods are available, such as preventive, chemical, physical, mechanical, cultural and biological. As several practices aim at a control with greater efficiency and less environmental impact, therefore technical knowledge is needed to determine how actions are applied. During the internship, we conducted or surveyed the main weeds in three properties in southern Tocantins. Along with the technical supervisor of the internship, the agricultural engineer Alex Sandro Dário, as well as the monitoring, regulation of the machinery used and the necessary recommendations for the control of the emerging flora.